Assessing coral sperm motility - Zuchowicz, Nikolas (Sci Rep, 2021)
The declining reproductive viability of corals threatens their ability to adapt to changing ocean conditions. It is vital that we monitor this viability quantitatively and comparatively. Computer-assisted sperm analysis (CASA) systems offer in-depth analysis used regularly for domestic and wildlife species, but not yet for coral. This study proposes quality control procedures and CASA settings that are effective for coral sperm analysis. To resolve disparities between CASA measurements and evaluations by eye, two negative effects on motility had to be resolved, slide adhesion (procedural) and sperm dilution (biological). We showed that the addition of bovine serum albumin, or caffeine, or both to fresh sperm reduced adhesion in the CASA cassettes, improved motility and motile sperm concentration (P < 0.0001), yet these additions did not affect measurements of total sperm concentration. Diluting coral sperm reduced sperm motility (P = 0.039), especially from heat-stressed corals. We found CASA concentration counts comparable to haemocytometer and flow cytometer measures (P = 0.54). We also found that motile sperm per egg is a useful predictor of fertilisation success, using cryopreserved sperm. Standard measurements of coral reproductive characteristics inform our understanding of the impacts of climate change on reef populations; this study provides a benchmark to begin this comparative work.